Building Employee Performance - Farhani, Farhani (International Review of Management and Marketing, 2019)
This research can provide information about leadership style, work motivation and organizational culture on employee performance at PT. Pos Indonesia (Persero) West Jakarta either partially or simultaneously (simultaneously) with X1 variable of leadership motivation, X2 variable of work motivation and X3 variable of organizational culture as independent variable, while Y dependent variable is employee performance. The research method used is an analysis that searches for direct influence over three independent variables and one dependent variable. Population of this research is employees of PT. Pos Indonesia (Persero) West Jakarta as respondents are employees of executives, managers and other employees with random sampling method of data with questionnaires to respondents. Influence will be done by using correlation method, regression, t test and F test assisted by SPSS application version 18.00. Thus, identified the magnitude of the influence of each variable (Style Leadership, Work Motivation and Organizational Culture) on Employee Performance. SPSS version calculation results version 18.00 indicates that each variable has an influence on employee performance with leadership style level is strong, strong work motivation and weak organization culture. Keywords: Leadership Style, Work Motivation, Organizational Culture, Employee Performance JEL Classifications: M12, M54, N75 DOI: https://doi.org/10.32479/irmm.8533